Edukasi dan Pelatihan Pengelolaan Sampah untuk Mengurangi Pembakaran Sampah di Kelurahan Mamboro Barat - Mustafa; Arianty, Ros; Amsal, Amsal (Education and Talent Development Center of Indonesia, 2025)
The issue of waste burning in Mamboro Barat Village remains a serious environmental concern, particularly due to limited access to adequate waste collection services and a lack of public awareness regarding the negative impacts of such practices. This community service initiative aims to enhance public knowledge and skills in environmentally friendly organic waste management through education and training in composting. The activity was conducted on 5 June 2025 and targeted the general public as well as participants of the Padat Karya programme. The implementation method was divided into three stages: preparation (coordination, material development, and logistics preparation), implementation (pre-test administration, educational lectures using PowerPoint presentations, composting training using vegetable scraps and dry leaves, and technical guidance), and evaluation (post-test to measure knowledge improvement). A total of 35 participants attended the entire series of activities. The pre-test results showed an average score of 59.66, which increased to 79.69 in the post-test, with an average improvement of 20.03 points. In addition to knowledge enhancement, participants also gained practical skills in processing organic waste into compost and increased awareness of the importance of sustainable waste management. Students actively participated as mentors and facilitators, strengthening the connection between educational institutions and the community. This activity made a positive contribution to fostering environmentally friendly behaviour through direct community involvement and capacity building. Active community participation in education and training has proven effective in driving behavioural change and opening opportunities for the development of community-based waste management systems in the future.